Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia - Yearsley, Gordon K.; Last, Peter R. (Zootaxa, 2006)
A new stingaree, Urolophus kapalensis sp. nov., is described from material collected off eastern Australia. It differs from the partially sympatric U. paucimaculatus, the only other known Urolophus with a bell-shaped internasal flap, in having a dorsal fin (absent in U. paucimaculatus), in coloration (e.g. with a V-shaped band across the interorbit, which is absent in U. paucimaculatus), and in a number of morphometric and meristic characters including: a narrower disc (disc width 4.6–5.0 times distance between first gill slits vs 5.1 in U. paucimaculatus), a longer stinging spine (11.8– 14.9 vs 9.3–11.5% TL), a shorter spiracle (0.8–1.0 vs 1.1–1.2 times orbit length), and more prespine vertebrae (86–95 vs 79–88). The two species are also distinguished by the cytochrome oxidase subunit 1 (CO1) gene with a divergence of 9%. The new Urolophus is medium-sized, and occurs from Cape Moreton (Qld) south to Disaster Bay (N.S.W.) in depths of 9–79 m.